Dinamika Implementasi Komunikasi Direktorat Jenderal Bimbingan Masyarakat Islam Kementerian Agama Dalam Pengelolaan Masjid di Kota Kisaran : (Studi Berdasarkan Keputusan Dirjen Bimas Islam Nomor DJ.II/802 Tahun 2014 tentang Standar Pembinaan Manajemen Masjid) - Kamalia; Hasnun Jauhari Ritonga; Fatma Yulia (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
This research aims to determine the dynamics of communication implementation by the Directorate General of Islamic Community Guidance, Ministry of Religion, in the management of mosques in Kisaran City. Based on the Decree of the Director General of Islamic Community Guidance Number DJ.II/802 of 2014 concerning Mosque Management Development Standards This research is qualitative with a descriptive approach. This research data was obtained from two main sources: primary data and secondary data. Primary data comes from a collection of data obtained directly through observations of natural phenomena in the research object. Meanwhile, secondary data is obtained through supporting information obtained indirectly, especially from literature and documents that are relevant to the research context. Data collection in this research used non-participant observation techniques. The data obtained will then be processed and analyzed through a process of reduction, presentation, and drawing conclusions. The results of this research indicate that the implementation of communication by the Directorate General of Islamic Community Guidance (Bimas Islam) of the Ministry of Religion plays a central role in maintaining and enhancing the strategic role of mosques as centers of religious and social activities in Kisaran City. This implementation process involves establishing conceptual understanding, introducing policies, continuous reporting and evaluation, providing incentives, cultural adaptation, and collaboration with various related entities. Effective communication plays a role in overcoming challenges, ensuring sustainable mosque management, and accelerating the achievement of mosque management development standards. This allows the mosque to continue to play a central role as a center for religious and social activities that contribute to the sustainable development of the Muslim community in Kisaran City.